Provisional Elemental Values for IAEA‐Sewage Sludge by Instrumental Neutron Activation Analysis. Issue 1 (13th August 2012) - Wasim, Mohammad; Arif, Mohammad; Iqbal, Sajid; Daud, Muhammad
<x xml:space="preserve">Abstract</x> The International Atomic Energy Agency (IAEA) organised a proficiency test (PT), IAEA‐CU‐2010‐02, for the determination of elements in sewage sludge. The PT sample was analysed by semi‐absolute standardless k0‐instrumental neutron activation analysis (k0‐INAA). Results for seven elements (As, Co, Cr, Fe, Hg, Se, Zn) were submitted to the IAEA by our laboratory. All of our results were scored 'acceptable' by the 'result evaluation criteria' adopted by the IAEA. The same analytical methodology produced quantitative results for twenty‐six additional elements. In total, thirty‐six elements were determined with uncertainty varying from 4 to 11%. This paper presents the provisional mass fractions of twenty‐six additional elements (Ag, Al, Br, Ca, Ce, Cl, Dy, Eu, Ga, Hf, I, K, La, Mg, Mn, Na, Rb, Sb, Sc, Sm, Ta, Tb, Th, V, U, W) not reported by the IAEA. The analytical methodology was discussed with important sources of spectral, nuclear and fission‐product interferences. It was shown that the important components of uncertainties were the k0 factor, Q0 factor, detector efficiency, mass and counting statistics. The methodology was validated by analysing the IAEA‐S7 reference material.